2013
DOI: 10.1007/s11150-013-9235-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying peer effects using spatial analysis: the role of peers on risky sexual behavior

Abstract: This paper explores the role of peer effects on early sexual debut for a sample of adolescents using data from the National Longitudinal Study on Adolescent Health (Add Health). Most studies analyzing peer influences ignore the “reflection” problem that occurs with studying peer effects. To address the reflection problem, this paper employs a spatial econometric approach to estimate a social interactions model. This is the first study in the literature on adolescent risky sexual behavior to use this approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…We also found that younger men in the camps who had older, rather than younger, friends in their networks were more likely to engage in concurrency. This finding is consistent with other studies showing that adolescents with older friendship networks are more likely to engage in sexual risk behaviors [7, 36]. Several studies from Tanzania have shown that young men engage in concurrency to prove their success with women to their peers and contribute to the norm that young men need multiple partners to satisfy their sexual needs [23, 54].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also found that younger men in the camps who had older, rather than younger, friends in their networks were more likely to engage in concurrency. This finding is consistent with other studies showing that adolescents with older friendship networks are more likely to engage in sexual risk behaviors [7, 36]. Several studies from Tanzania have shown that young men engage in concurrency to prove their success with women to their peers and contribute to the norm that young men need multiple partners to satisfy their sexual needs [23, 54].…”
Section: Discussionsupporting
confidence: 90%
“…The theory of social influence suggests that men may behave according to the behaviors or expectations of their social networks [5]. Empirical support for the theory among studies of male adolescents have found an association between networks and several HIV risk behaviors, including having sex with multiple partners [6], early sexual debut [7], and condomless sex [8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social networks have been shown to influence a number of HIV risk behaviors including condom use (Barrington et al, 2009), sexual partnership concurrency (Yamanis, Fisher, Moody, & Kajula, 2015), early sexual debut (Ajilore, 2015), as well as drug use and needle sharing (De, Cox, Boivin, Platt, & Jolly, 2007; Lakon, Ennett, & Norton, 2006). These studies have highlighted the important role that peer characteristics (Ajilore, 2015), perceived descriptive norms of network members (Barrington et al, 2009), network structure and composition (De et al, 2007), as well as the interaction between network closeness and descriptive norms (Yamanis et al, 2015) may play in shaping HIV risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well acknowledged that adolescents tend to adopt health behaviours that are similar to their friends' behaviours, and this has been shown in a range of domains such as substance use, nutrition, and sexual activity (Ajilore, 2015;Clark & Loheac, 2007;Ennett et al, 2006;Kobus, 2003;McGloin et al, 2014;Simons-Morton & Farhat, 2010; T. W. Valente et al, 2004). Moreover, exposure to substance use is associated with the structural position of an adolescent in the network.…”
Section: Introductionmentioning
confidence: 99%